Coaching for instructional improvement in Selangor and Sabah / Salwati Shafee - Salwati , Shafee (2019)
This study looks at the implementation of coaching in Malaysian schools. It focuses on the practice of coaching and its relation to the improvement of teachers' classroom practices in primary and secondary schools in Selangor and Sabah. A total of 470 teachers and coaches (SISC+) from 10 District Education Department in Selangor and 24 District Education Department in Sabah were involved as respondents in this study. This quantitative study is based on survey method. The research data were obtained through a set of questionnaire as the research instrument of the study. The instrument is used to measure different variables of this study which is adapted based on 5 instruments from previous studies (Reed, 2015; Frye, 2015; Eismin, 2015; Dugan, 2010 & Parman, 2015). To answer research questions 1, 2 and 3, descriptive statistics were analyzed using the Statistical Package for Social Sciences (SPSS) Version 23.0 based on the mean value and standard deviation for the purpose of measuring the level of coaching elements and the impact on all the variables related to coaching. Whereas, inferential analysis for research questions 4, 5, 6 and 7, data were undertaken using Structural Equation Modeling PLS 3.0 to analyse the relationship between the variables as well as to look at the mediation and moderating effect of certain variables. The findings show that the level of guidance in schools in Selangor and Sabah is high for every construct measured based on mean score and standard deviation. Analysis of findings also shows the level of knowledge and skills of the coach are of moderate level. In addition, the findings show that the practice of coaching in schools in Selangor and Sabah is at the "implementation" level which indicates that coaching is not a school culture. However, the findings also showed that there were no significant differences in the perceptions of teachers and coaches based on state or roles. The findings of the SEM PLS analysis show that there is a significant and positive relationship between coaching and other variables such as instructional improvement, continuous professional learning, leadership, learning outcomes, school climate and the implementation of coaching practice. The analysis of the elements of coaching shows that all the elements of coaching were significant towards other variables except for element reflect. An analysis of the findings based on indirect effects shows that coaching has a partial mediating effect in the relationship between continuous professional learning, leadership, school climate and the level of implementation of coaching practices towards instructional improvement, learning outcomes and school improvement. The PLS SEM analysis on moderation also shows that there is no moderating effect for teaching experience and frequency of training towards instructional improvement. Finally, some research implications for stake holders are also discussed based on theoretical and practical implications. Some advanced research recommendations have also been suggested so that the findings of future studies will be more meaningful and adds to the body of literature of similar field.